A comparison of methods used to determine percent body fat, minimum wrestling weight, and lowest allowable weight class - Cutrufello, P. T.; Landram, M. J.; Venezia, A. C.; Dixon, C. B. (The Journal of Strength and Conditioning Research, 2021)
The National Collegiate Athletic Association's weight management program allows for the use of skinfold measurements (SF), air displacement plethysmography (ADP), and hydrostatic weighing in the assessment of percent body fat (%BF) and determination of a wrestler's minimum wrestling weight (MWW). Dual energy x-ray absorptiometry (DXA) and ultrasound (US) may offer alternative assessment methods. The purpose of this study was to examine %BF, MWW, and the lowest allowable weight class as determined by SF, ADP, DXA, and US. Thirty-three college-aged men (20.8 ± 1.1 years) participated. Urine specific gravity (Usg) was assessed to ensure proper hydration (1.006 ± 0.006). Percent body fat and MWW were then determined using the 4 assessment methods. Each method was significantly different from one another (p < 0.05) with the exception of ADP compared with SF (17.6 ± 7.1% vs. 17.4 ± 6.3%, p = 1.000) and DXA compared with US (20.5 ± 6.2% vs. 19.2 ± 7.5%, p = 0.124). DXA (68.6 ± 7.1 kg) and US (69.3 ± 6.0 kg) determined the lowest MWW, whereas those determined by SF (70.8 ± 6.8 kg) and ADP (70.9 ± 6.6 kg) were significantly greater (p< 0.05). The SEEs for MWW when compared with SF were 3.2, 3.4, and 2.4 kg for ADP, DXA, and US, respectively. Compared with SF, DXA and US would allow wrestlers to certify at a lower weight class 64 and 33% of the time, respectively. When comparing the approved methods (SF and ADP), approximately 50% of subjects would certify at a different weight class depending on the method used. The use of different methods in assessing %BF offer a wide variability in the determination of MWW.